Field Measurements of Sound Insulation in Large, Open Rooms. Issue 3 (September 2014) - Zambon, G.; Angelini, F.; Belingheri, A.; Benocci, R.
The international standards governing the measurement of sound insulation in buildings (ISO 140) do not explicitly cover the methodology of taking measurements in large open rooms. A building with open plan floors, each of about 1300 m 2, is considered here. The ISO 140-14 standard, through an analysis of sound level distribution, allowed smaller partitions to be identified and used as reference volumes. Different index calculation methods allowed critical issues to be highlighted. The impact sound index was strongly affected by geometry (i.e., volume); therefore, its calculation using different virtual volumes gave differing results. Furthermore, the index calculated using the logarithmic average of the indices for each virtual volume and an extended analysis of measurements over the entire floor provided different results. The airborne sound insulation index was demonstrated to be independent of the choice of virtual volumes; it could be consistently calculated using either the logarithmic average or the extended analysis.